Planning accelerated reliability tests for mission-oriented systems subject to degradation and shocks. (2nd January 2020) - Zhao, Xiujie; He, Kangzhe; Kuo, Way; Xie, Min
Abstract: This article presents a novel accelerated reliability testing framework for mission-oriented systems. The system to be tested is assumed to suffer from cumulative degradation and traumatic shocks with increasing intensity. We propose a new optimality criterion that minimizes the asymptotic variance of the predicted reliability evaluated at the mission's end time. Two usage scenarios are considered in this study: one is to assume that systems are brand new at the start of the mission and the other is that systems are randomly selected from used ones under pre-determined policies. Optimal test plans for both scenarios are obtained via delta methods by utilizing the Fisher information. The global optimality of test plans is verified using general equivalence theorems. A revisited example of a carbon-film resistor is presented to illustrate the efficiency and robustness of optimal test plans for both new and randomly aged systems. The result shows that the test plan tends to explore more on lower stress levels for randomly aged systems. Furthermore, we conduct simulation studies and explore compromise test plans for the example.